Peran Media Sebagai Pembujuk, Membangun Popularitas, Investigator dan Hiburan - junaidi (At-Tabayyuun: Journal Islamic Studies, 2019)
The complexity of the effects of mass media influence penetrated almost all aspects of life, not only in the world of politics, economics, law and education, mass melainkanmedia also able to regulate human life, from waking to sleep again. How not, the media set to be used Sampho brands, car brands should be purchased, and even how we should be acting as a political figure, investigate the perpetrators of crimes and presenting entertainments desired audiences. That is why, not only members of the media are itching will determine what information is delivered to their audience, but also the public relations officer (public relations) also chimed offer what ads would be submitted to the public media.